PERTANGGUNGJAWABAN TINDAK PIDANA KORPORASI YANG MELAKUKAN KEGIATAN PERTAMBANGAN DILUAR TITIK KOORDINAT IJIN OPERASI PRODUKSI - DJAINUDIN WIJAYA (Fakultas Hukum Universitas Narotama, 2021)
The aim of this research is to find out the meaning of corporate criminal liability in Indonesian laws and regulations. This study uses a normative juridical method with a statute approach, a case approach, and a comparative approach. The primary, secondary, and tertiary legal materials obtained by the author will be analyzed using teleological or sociological interpretation techniques with interpretations that consider the meaning of the law to be determined based on social objectives. The results of this study indicate that the overall regulation of criminal responsibility for the management of mining companies in the Mining Law does not explicitly and concretely explain the sanctions imposed by both corporations and mining company managers.Keywords: Accountability; Corporation; Mining Outside the coordinate point of the production operation permit